Reopening America's Schools During the COVID-19 Pandemic: Protecting Asian Students From Stigma and Discrimination - Akiba, Daisuke (Frontiers in Sociology, 2020)
The COVID-19 outbreak has prompted a rise in stigma and discrimination against people of Asian descent in many areas in the world, including the United States . Anti-Asian hate incidents, which have ranged from verbal attacks, refusal of service to physical assault, continue to transpire in the U.S., and they put psychological and physical wellbeing of Asian children at increased risk. Discussions toward reopening of U.S. schools thus far, however, seem to have exclusively included the infection-related concerns and pedagogical consequences of continued disruptions in face-to-face instructions. Hence, educators, policymakers and other stakeholders need to have plans in place to ensure that reopening of schools will be a smooth experience for students of all backgrounds.